A safe and effective treatment combination of neoadjuvant therapy and surgical resection for metastatic TFE3-rearranged renal cell carcinoma:a case report - Yang, Haiyang; Dong, Xiang; Pan, Xinghe; Ma, Wenliang; Pan, Jun; Guo, Hongqian; Gan, Weidong (Frontiers in Oncology, 2023)
TFE3-rearranged renal cell carcinoma (RCC) is a rare subtype of renal tumor that primarily affects young women and is characterized by early metastasis and a poor prognosis. This case study presents a 29-year-old woman diagnosed with TFE3rearranged RCC, who initially presented with painless gross hematuria. Computed Tomography (CT) imaging revealed the presence of a solid mass in the left kidney along with retroperitoneal metastasis. The patient received axitinib, a vascular endothelial growth factor receptor-tyrosine kinase inhibitor (VEGFR-TKI), as first-line neoadjuvant therapy. Subsequent testing confirmed positive expression of programmed death-1 protein L1 (PDL1), leading to the addition of tislelizumab, a PD1 inhibitor, to the treatment regimen. After 8 months, the patient's tumor size and metastases exhibited significant reduction, providing a favorable opportunity for subsequent surgical intervention. The tumor was classified as IV (pT3aN0M1) based on the pathologic stage of the American Joint Committee on Cancer (AJCC, 8th edition, 2017). The patient achieved long-term survival through combined systemic therapy involving surgery and neoadjuvant treatment. At the 30-month follow-up, there was no evidence of tumor recurrence or metastasis.